THE MASTER OF DISTANCE EDUCATION PROGRAM: A COLLABORATION BETWEEN THE UNIVERSITY OF MARYLAND UNIVERSITY COLLEGE AND OLDENBURG UNIVERSITY - Rubin, Eugene; Bernath, Ulrich; Parker, Mark (Online Learning, 2004)
On November 15, 2003, The Master of Distance Education (MDE) program at the University of Maryland University College (UMUC) received the 2003 Sloan-C award for Most Outstanding Online Teaching and Learning Program. This award was given to the MDE “for an asynchronous, student-centered online graduate program that responds to the worldwide need for qualified managers of distance education programs in industry and academe.” This paper provides information about the program, the partnership and the curriculum.